Folic acid and deoxycholic acid derivative modified Fe3O4 nanoparticles for efficient pH-dependent drug release and multi-targeting against liver cancer cells. Issue 63 (14th December 2021) - Wang, Xiaoyu; Ma, Qing; Wen, Chaochao; Gong, Tao; Li, Jing; Liang, Wenting; Li, Meining; Wang, Yuyao; Guo, Rui
Abstract : A nano-drug carrier, FDCA-FA-MNPs was constructed by modifying Fe3 O4 magnetic nanoparticles (MNPs) with formyl deoxycholic acid (FDCA) and folic acid (FA) with double-targeting, pH-triggered drug release and excellent tumor cell killing efficiency. Abstract : The novel nano-drug carrier (FDCA-FA-MNPs) was constructed by grafting formyl deoxycholic acid (FDCA) and folic acid (FA) on the surface of Fe3 O4 magnetic nanoparticles (MNPs), possessing the advantages of superparamagnetism, good stability, low cytotoxicity and good blood compatibility. The hydrophobic anti-cancer drug doxorubicin hydrochloride (DOX) was successfully loaded onto FDCA-FA-MNPs through supramolecular interactions (hydrogen bond between FDCA and drug and hydrophobic interaction and π–π stacking between drug and drug). The drug loading amount and drug loading capacity were 509.1 mg g −1 and 33.73 wt%, respectively. In addition, drug release had a pH responsive and controllable release performance, the release rate at pH 5.3 (45.6%) was four times that at pH 7.4 (11.5%), and the tumor microenvironment was favorable for drug release. More importantly, the novel nano-drug carrier combined the hepatocellular targeting of FDCA, the cancer cell targeting of FA, and the magnetic targeting of Fe3 O4, showing excellent cancer-killing efficiency (78%) in vitro . Therefore, the nano-drug carrier synthesized in this paper has potential practical application value in the targeted therapy of liver cancer.